Analisis Filosofis Lambang Institut Agama Islam Negeri (IAIN) Pontianak - Fitriyanto, Andry; Septian Utut (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
This paper is part and development of the research results entitled Historical Map of Pontianak IAIN Policy Directions. Contains a discussion of the symbol of IAIN Pontianak as a symbol of institutional identity. The symbol is termed as a sign which is a medium of communication between the owner and the public. Some messages are conveyed and captured by everyone who sees it. This study uses Charles Sanders Peirce's semiotic analysis method with a triangle meaning. Includes ground (sign), denotatum (object), and interpretant. These three aspects are used to see the elements of the symbols contained in the IAIN Pontianak symbol. Also to see how the work and the relationship between these elements present a certain meaning to the public. The results of this study are; First, the IAIN Pontianak symbol consists of a combination of picture marks and letter marks. picture mark consisting of a flower symbol with six outers and five inner petals, an equator monument, a carved fern motif typical of West Kalimantan, a nib, open book/book. While the letter mark is the words